2012
DOI: 10.3168/jds.2011-4947
|View full text |Cite
|
Sign up to set email alerts
|

Stability of milk fat globule membrane proteins toward human enzymatic gastrointestinal digestion

Abstract: The milk fat globule membrane (MFGM) fraction refers to the thin film of polar lipids and membrane proteins that surrounds fat globules in milk. It is its unique biochemical composition that renders MFGM with some beneficial biological activities, such as anti-adhesive effects toward pathogens. However, a prerequisite for the putative bioactivity of MFGM is its stability during gastrointestinal digestion. We, therefore, subjected MFGM material, isolated from raw milk, to an in vitro enzymatic gastrointestinal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
49
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 43 publications
(53 reference statements)
2
49
0
Order By: Relevance
“…Further investigation is also needed to conclude whether MUC1 levels or the degree of glycosylation of MUC1 on milk-derived exosomes impact viral infection. It has been shown that several of the molecules found on milk-derived exosomes, such as MUC1 and CD36, are more resistant to gastrointestinal digestion when associated with the membrane of milk fat globulins [30]. In addition, the higher gastric pH of the newborn relative to the adult [31], as well the finding that exosomes are longlasting in vivo [32], suggest that exosomes might be protected from degradation in the stomach and could potentially impact the immune system of the breastfed child.…”
Section: Discussionmentioning
confidence: 99%
“…Further investigation is also needed to conclude whether MUC1 levels or the degree of glycosylation of MUC1 on milk-derived exosomes impact viral infection. It has been shown that several of the molecules found on milk-derived exosomes, such as MUC1 and CD36, are more resistant to gastrointestinal digestion when associated with the membrane of milk fat globulins [30]. In addition, the higher gastric pH of the newborn relative to the adult [31], as well the finding that exosomes are longlasting in vivo [32], suggest that exosomes might be protected from degradation in the stomach and could potentially impact the immune system of the breastfed child.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, defatted bovine MFGM has previously been digested in vitro and SDS gels have been used to analyse the protein and glycoprotein composition post-digestion. Coomassie-stained gels demonstrated hydrolysis of MFGM proteins after 20 min of pepsin digestion; however, many bands corresponding to MFGM glycoproteins were observed on the PAS stained gel indicating incomplete hydrolysis and partial resistance to the action of pepsin (Le et al, 2012). In vitro intestinal digestion led to hydrolysis of all remaining MFGM glycoproteins with the exception of Muc1 (Le et al, 2012).…”
Section: Dmfgm Reduced the Association Of E Coli O157:h7 With Ht-29 mentioning
confidence: 90%
“…Coomassie-stained gels demonstrated hydrolysis of MFGM proteins after 20 min of pepsin digestion; however, many bands corresponding to MFGM glycoproteins were observed on the PAS stained gel indicating incomplete hydrolysis and partial resistance to the action of pepsin (Le et al, 2012). In vitro intestinal digestion led to hydrolysis of all remaining MFGM glycoproteins with the exception of Muc1 (Le et al, 2012). Similarly, PAS staining of whole MFGM indicated resistance of CD36 and Muc1 to in vivo gastric digestion (Gallier et al, 2013a) and potential resistance of Muc1 to in vivo intestinal digestion (Gallier et al, 2013b).…”
Section: Dmfgm Reduced the Association Of E Coli O157:h7 With Ht-29 mentioning
confidence: 96%
“…After concentration (a volume reduction ratio of 20) and diafiltration (four diafiltration steps), the recovery of phospholipids was calculated to be between 95 and 99%. However, other studies showed that some membrane proteins were susceptible to enzymatic degradation (Corredig & Dalgleish, 1997b;Kobylka & Carraway, 1973;Le et al, 2012;Shimizu, Yamauchi, & Kanno, 1979;Vanderghem et al, 2011). Therefore, the simultaneous permeation of MFGM proteins during ultracentrifugation of hydrolysed buttermilk whey needs to be further explored.…”
Section: Ultrafiltration Of Buttermilk and Buttermilk Wheymentioning
confidence: 94%